Analisis Keterampilan Guru dalam Penggunaan Teknologi yang Mendukung Pembelajaran Daring Guru Kelas V SDN 1 Pakel - Nugrananda Janattaka; Erlis Wahyu Puji Santoso (Arden Jaya Publisher, 2022)
Teachers are very noble professions and have noble values in society, therefore teachers are required to be creative and innovative in carrying out teaching to students. Digital learning media or modern technology is one of the learning tools that must be mastered and used by teachers when learning in this day and age, namely learning during a pandemic. Therefore, the skills of a teacher in the use of digital learning media during a pandemic are very important in learning and influencing the thematic learning process. The objectives of this study are 1) To find out how the implementation and skills of teachers in the use of online learning media at SDN 1 Pakel, 2) To find out the inhibiting factors in the use of online learning at SDN 1 Pakel. The type of research used by the researcher is qualitative, namely research that examines data in depth to understand the emerging phenomena. The subjects in this study were teachers of SDN 1 Pakel. As for data collection techniques, using interviews and documentation. The results of the analysis of this study indicate that teachers experience several obstacles in the online learning process, this can be seen from the teacher's skills in using digital learning media, there are several difficulties experienced when doing online learning. This difficulty lies in teachers, students, and parents. Difficulties include; The link provided by the teacher cannot be accessed by students, quotas, networks, old school android cellphones, assignments not sent according to schedule, forgetting, cellphones brought by parents, lack of assistance from parents.